Analyzing Higher Order Thinking Skills in Reading Exercises of Indonesian EFL Textbook - Maryamah, Siti Ega; Wati, Setyo; Suharto, Pipit Prihartanti (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
To face 21st-century challenges, the elements involved in the pedagogical approach, such as textbooks, must enable students to enhance their higher-order thinking skills (HOTS). This qualitative research aims to determine to what extent HOTS is incorporated in an Indonesian EFL textbook. The comprehension questions of reading texts in the textbook for 7th grade were analyzed through content analysis based on the six cognitive domains in the revised Bloom’s Taxonomy (Anderson & Krathwohl, 2001). The findings of the study revealed: (1) 80,4% of the reading comprehension questions classified as lower-order thinking skills (LOTS), particularly level 1 (remember) and level 2 (understanding), whereas 19,6% of the questions classified as higher-level thinking skills, primarily the level 4 (analyze) and level 5 (evaluate). (2) The reading comprehension check questions were organized systematically from lower-thinking to higher-thinking skills, which develops students’ comprehension and provides instructional organization for teaching texts to English teachers. This study is expected to benefit English teachers, textbook authors, and future researchers to elaborate on implementing HOTS in English language teaching and learning.